Air pollution, residents’ concern and commercial health insurance’s sustainable development - Ren, Tianxing; Zhao, Qiang; Wang, Wenqing; Ding, Xuemeng (Frontiers in Environmental Science, 2023)
This paper empirically analyses the impact and mechanism of air pollution on Chinese commercial health insurance’s sustainable development. The analysis is performed with the IV-Probit and IV-Tobit models using thermal inversion as an instrumental variable for air pollution, with Chinese households as the study population and 2018 as the study period. The findings show that: (1) an increase in PM2.5 concentration has a significant positive impact on households' willingness to participate in purchasing commercial health insurance, with each 1% increase in PM2.5 concentration increasing the likelihood of households participating in purchasing commercial health insurance by 1.49%; (2) an increase in PM2.5 concentration has a significant positive impact on household participation in purchasing commercial health insurance, with each 1% increase in PM2.5 concentration associated with a 11.48% increase in household expenditure on commercial health insurance as a proportion of total income; and (3) Residents’ concern is an important channel linking air pollution to commercial health Insurance’s sustainable development, where pollution reporting plays a negative transmission role, protective behaviors play a positive transmission role, and healthy depreciation plays a positive transmission role.